2004
DOI: 10.1016/j.jcat.2004.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of manganese and iron into the zirconia lattice in promoted sulfated zirconia catalysts

Abstract: Two series of Mn-or Fe-promoted zirconia samples were prepared, (i) a series of sulfated-free reference compounds via co-precipitation of aqueous solutions containing zirconium and the promoter cation, and (ii) a series of catalysts via incipient-wetness impregnation of a sulfated zirconium hydroxide. The promoter content was varied between 0 and 5 wt% metal. All promoter-containing materials were calcined at 923 K. The reference materials contained mainly isolated Mn or Fe species incorporated into the zircon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 72 publications
(71 reference statements)
4
62
0
Order By: Relevance
“…The activity of SZ can be improved by 1 to 2 orders of magnitude through the addition of small amounts of a second metal component as promoter, e.g., Mn or Fe [12][13][14]. It has been found that one of the effects of these promoters is the stabilization of the tetragonal (cubic) phase by incorporation of the Mn or Fe cations into the zirconia lattice [15,16]. Furthermore, mechanical stress in the form grinding, milling, or pressing-typical laboratory practices for homogenization or wafer fabrication-can convert tetragonal into monoclinic zirconia, and the phase change is accompanied by a decrease of catalytic activity for n-butane isomerization [17].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of SZ can be improved by 1 to 2 orders of magnitude through the addition of small amounts of a second metal component as promoter, e.g., Mn or Fe [12][13][14]. It has been found that one of the effects of these promoters is the stabilization of the tetragonal (cubic) phase by incorporation of the Mn or Fe cations into the zirconia lattice [15,16]. Furthermore, mechanical stress in the form grinding, milling, or pressing-typical laboratory practices for homogenization or wafer fabrication-can convert tetragonal into monoclinic zirconia, and the phase change is accompanied by a decrease of catalytic activity for n-butane isomerization [17].…”
Section: Introductionmentioning
confidence: 99%
“…The various phases of zirconia are stable in various ranges of oxygen vacancy concentration. Promoter ions such as Fe 3+ or Mn x+ (x<4) have also been shown to stabilize the high temperature phases of zirconia [47][48][49][50][51]. They are incorporated into the lattice similarly to Y 3+ , and for charge balance, oxygen vacancies are formed.…”
Section: Zirconia Phase Chemistry and Catalytic Activitymentioning
confidence: 99%
“…Promoters with a valence lower than + IV enhance the stability of the tetragonal phase because oxygen vacancies are generated. The incorporation of the iron and manganese cations leads to a smaller unit cell size of the tetragonal phase, mostly through reduction of the unit cell constant c [47]. The doping affects the stability in a second way because the reduced unit cell size will affect the surface energy.…”
Section: Effects Of Adsorbates On Oxide Surface Energy and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It has been found that it is not just the strength of the acid but also the type of acidity (Brønsted or Lewis) that matters for improved activity and selectivity. The inclusion of superacidity in solids has attracted great attention.…”
Section: Introductionmentioning
confidence: 99%